Calculator search results

Formula
Solve the quadratic equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Number of solution
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Relationship between roots and coefficients
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Graph
$y = 2 \left ( x + 3 \right ) ^ { 2 }$
$y = 54$
$x$-intercept
$\left ( - 3 , 0 \right )$
$y$-intercept
$\left ( 0 , 18 \right )$
Minimum
$\left ( - 3 , 0 \right )$
Standard form
$y = 2 \left ( x + 3 \right ) ^ { 2 }$
$2 \left( x+3 \right) ^{ 2 } = 54$
$\begin{array} {l} x = - 3 + 3 \sqrt{ 3 } \\ x = - 3 - 3 \sqrt{ 3 } \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } = 54$
$ $ Organize the expression $ $
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 12 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 18 } = 54$
$2 x ^ { 2 } + 12 x + 18 = \color{#FF6800}{ 54 }$
$ $ Move the expression to the left side and change the symbol $ $
$2 x ^ { 2 } + 12 x + 18 \color{#FF6800}{ - } \color{#FF6800}{ 54 } = 0$
$2 x ^ { 2 } + 12 x + \color{#FF6800}{ 18 } \color{#FF6800}{ - } \color{#FF6800}{ 54 } = 0$
$ $ Subtract $ 54 $ from $ 18$
$2 x ^ { 2 } + 12 x \color{#FF6800}{ - } \color{#FF6800}{ 36 } = 0$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 12 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 36 } = \color{#FF6800}{ 0 }$
$ $ Divide both sides by the coefficient of the leading highest term $ $
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 18 } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 18 } = \color{#FF6800}{ 0 }$
$ $ Convert the quadratic expression on the left side to a perfect square format $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 18 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 18 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$ $ Organize the expression $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 27 }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 27 }$
$ $ Solve quadratic equations using the square root $ $
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \pm \sqrt{ \color{#FF6800}{ 27 } }$
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } = \pm \sqrt{ \color{#FF6800}{ 27 } }$
$ $ Solve a solution to $ x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ 3 } \sqrt{ \color{#FF6800}{ 3 } } \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ 3 } \sqrt{ \color{#FF6800}{ 3 } } \color{#FF6800}{ - } \color{#FF6800}{ 3 }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \sqrt{ \color{#FF6800}{ 3 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \sqrt{ \color{#FF6800}{ 3 } } \end{array}$
$\begin{array} {l} x = - 3 + 3 \sqrt{ 3 } \\ x = - 3 - 3 \sqrt{ 3 } \end{array}$
Calculate using the quadratic formula
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } = 54$
$ $ Organize the expression $ $
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 12 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 18 } = 54$
$2 x ^ { 2 } + 12 x + 18 = \color{#FF6800}{ 54 }$
$ $ Move the expression to the left side and change the symbol $ $
$2 x ^ { 2 } + 12 x + 18 \color{#FF6800}{ - } \color{#FF6800}{ 54 } = 0$
$2 x ^ { 2 } + 12 x + \color{#FF6800}{ 18 } \color{#FF6800}{ - } \color{#FF6800}{ 54 } = 0$
$ $ Subtract $ 54 $ from $ 18$
$2 x ^ { 2 } + 12 x \color{#FF6800}{ - } \color{#FF6800}{ 36 } = 0$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 12 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 36 } = 0$
$ $ Bind the expressions with the common factor $ 2$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 18 } \right ) = 0$
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 18 } \right ) = \color{#FF6800}{ 0 }$
$ $ Divide both sides by $ 2$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 6 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 18 } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 6 \pm \sqrt{ 6 ^ { 2 } - 4 \times 1 \times \left ( - 18 \right ) } } { 2 \times 1 } }$
$ $ Organize the expression $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 6 \pm \sqrt{ 108 } } { 2 \times 1 } }$
$x = \dfrac { - 6 \pm \sqrt{ \color{#FF6800}{ 108 } } } { 2 \times 1 }$
$ $ Organize the part that can be taken out of the radical sign inside the square root symbol $ $
$x = \dfrac { - 6 \pm \color{#FF6800}{ 6 } \sqrt{ \color{#FF6800}{ 3 } } } { 2 \times 1 }$
$x = \dfrac { - 6 \pm 6 \sqrt{ 3 } } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
$ $ Multiplying any number by 1 does not change the value $ $
$x = \dfrac { - 6 \pm 6 \sqrt{ 3 } } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 6 \pm 6 \sqrt{ 3 } } { 2 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 6 + 6 \sqrt{ 3 } } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 6 - 6 \sqrt{ 3 } } { 2 } } \end{array}$
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { - 6 + 6 \sqrt{ 3 } } { 2 } } \\ x = \dfrac { - 6 - 6 \sqrt{ 3 } } { 2 } \end{array}$
$ $ Do the reduction of the fraction format $ $
$\begin{array} {l} x = \color{#FF6800}{ \dfrac { - 3 + 3 \sqrt{ 3 } } { 1 } } \\ x = \dfrac { - 6 - 6 \sqrt{ 3 } } { 2 } \end{array}$
$\begin{array} {l} x = \dfrac { - 3 + 3 \sqrt{ 3 } } { \color{#FF6800}{ 1 } } \\ x = \dfrac { - 6 - 6 \sqrt{ 3 } } { 2 } \end{array}$
$ $ If the denominator is 1, the denominator can be removed $ $
$\begin{array} {l} x = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \sqrt{ \color{#FF6800}{ 3 } } \\ x = \dfrac { - 6 - 6 \sqrt{ 3 } } { 2 } \end{array}$
$\begin{array} {l} x = - 3 + 3 \sqrt{ 3 } \\ x = \color{#FF6800}{ \dfrac { - 6 - 6 \sqrt{ 3 } } { 2 } } \end{array}$
$ $ Do the reduction of the fraction format $ $
$\begin{array} {l} x = - 3 + 3 \sqrt{ 3 } \\ x = \color{#FF6800}{ \dfrac { - 3 - 3 \sqrt{ 3 } } { 1 } } \end{array}$
$\begin{array} {l} x = - 3 + 3 \sqrt{ 3 } \\ x = \dfrac { - 3 - 3 \sqrt{ 3 } } { \color{#FF6800}{ 1 } } \end{array}$
$ $ If the denominator is 1, the denominator can be removed $ $
$\begin{array} {l} x = - 3 + 3 \sqrt{ 3 } \\ x = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 3 } \sqrt{ \color{#FF6800}{ 3 } } \end{array}$
$ $ 2 real roots $ $
Find the number of solutions
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } = 54$
$ $ Organize the expression $ $
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 12 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 18 } = 54$
$2 x ^ { 2 } + 12 x + 18 = \color{#FF6800}{ 54 }$
$ $ Move the expression to the left side and change the symbol $ $
$2 x ^ { 2 } + 12 x + 18 \color{#FF6800}{ - } \color{#FF6800}{ 54 } = 0$
$2 x ^ { 2 } + 12 x + \color{#FF6800}{ 18 } \color{#FF6800}{ - } \color{#FF6800}{ 54 } = 0$
$ $ Subtract $ 54 $ from $ 18$
$2 x ^ { 2 } + 12 x \color{#FF6800}{ - } \color{#FF6800}{ 36 } = 0$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 12 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 36 } = \color{#FF6800}{ 0 }$
$ $ Determine the number of roots using discriminant, $ D=b^{2}-4ac $ from quadratic equation, $ ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \color{#FF6800}{ 12 } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 36 } \right )$
$D = \color{#FF6800}{ 12 } ^ { \color{#FF6800}{ 2 } } - 4 \times 2 \times \left ( - 36 \right )$
$ $ Calculate power $ $
$D = \color{#FF6800}{ 144 } - 4 \times 2 \times \left ( - 36 \right )$
$D = 144 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 36 } \right )$
$ $ Multiply the numbers $ $
$D = 144 + \color{#FF6800}{ 288 }$
$D = \color{#FF6800}{ 144 } \color{#FF6800}{ + } \color{#FF6800}{ 288 }$
$ $ Add $ 144 $ and $ 288$
$D = \color{#FF6800}{ 432 }$
$\color{#FF6800}{ D } = \color{#FF6800}{ 432 }$
$ $ Since $ D>0 $ , the number of real root of the following quadratic equation is 2 $ $
$ $ 2 real roots $ $
$\alpha + \beta = - 6 , \alpha \beta = - 18$
Find the sum and product of the two roots of the quadratic equation
$\color{#FF6800}{ 2 } \left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 3 } \right ) ^ { \color{#FF6800}{ 2 } } = 54$
$ $ Organize the expression $ $
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 12 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 18 } = 54$
$2 x ^ { 2 } + 12 x + 18 = \color{#FF6800}{ 54 }$
$ $ Move the expression to the left side and change the symbol $ $
$2 x ^ { 2 } + 12 x + 18 \color{#FF6800}{ - } \color{#FF6800}{ 54 } = 0$
$2 x ^ { 2 } + 12 x + \color{#FF6800}{ 18 } \color{#FF6800}{ - } \color{#FF6800}{ 54 } = 0$
$ $ Subtract $ 54 $ from $ 18$
$2 x ^ { 2 } + 12 x \color{#FF6800}{ - } \color{#FF6800}{ 36 } = 0$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 12 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 36 } = \color{#FF6800}{ 0 }$
$ $ In the quadratic equation $ ax^{2}+bx+c=0 $ , if the two roots are $ \alpha, \beta $ , then it is $ \alpha + \beta =-\dfrac{b}{a} $ , $ \alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 12 } { 2 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { - 36 } { 2 } }$
$\alpha + \beta = - \color{#FF6800}{ \dfrac { 12 } { 2 } } , \alpha \beta = \dfrac { - 36 } { 2 }$
$ $ Reduce the fraction $ $
$\alpha + \beta = - \color{#FF6800}{ 6 } , \alpha \beta = \dfrac { - 36 } { 2 }$
$\alpha + \beta = - 6 , \alpha \beta = \color{#FF6800}{ \dfrac { - 36 } { 2 } }$
$ $ Reduce the fraction $ $
$\alpha + \beta = - 6 , \alpha \beta = \color{#FF6800}{ - } \color{#FF6800}{ 18 }$
$ $ 그래프 보기 $ $
Graph
Solution search results
search-thumbnail-If the sum of two consecutive 
numbers is $45$ and one number is $X$ 
.This statement in the form of 
equation $1s:$ 
$\left(1$ Point) $\right)$ 
$○5x+1$ $1eft\left(x+1$ $r1gnt\right)=45s$ 
$○sx+1ef\left(x+2$ $r1gnt\right)=145s$ 
$sx+1x=45s$
7th-9th grade
Algebra
search-thumbnail-$s|ef\left(-1n$ $\left($ }\right)^{50}\ $\right)$ \ | | is\ equal\ to\ $S$ 
$s1S$ 
$S-1S$ 
$s2S$ 
$s50s$
7th-9th grade
Other
Have you found the solution you wanted?
Try again
Try more features at QANDA!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo